2008
DOI: 10.2337/dc07-2251
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term N-Acetylcysteine and l-Arginine Administration Reduces Endothelial Activation and Systolic Blood Pressure in Hypertensive Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Reactive oxygen and nitric oxide (NO) have recently been considered to be involved in the cardiovascular complications of patients with type 2 diabetes, as NO is thought to lose its beneficial physiological effects in the presence of oxygen radicals. For this reason, we tested the effects of L-arginine (ARG) and N-acetylcysteine (NAC) administration in increasing NO bioavailability by reducing free radical formation. RESEARCH DESIGN AND METHODS-A double-blind study was performed on 24 male patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 23 publications
(17 reference statements)
2
86
0
2
Order By: Relevance
“…The combination of L-argentine and NAC resulted in reduction of both systolic and diastolic blood pressure. Furthermore, a significant decrease in other risk factors of coronary artery disease such as total and LDL-C levels was observed (29). Also, our study showed the reduction of SBP and serum TG levels compared to the control group.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The combination of L-argentine and NAC resulted in reduction of both systolic and diastolic blood pressure. Furthermore, a significant decrease in other risk factors of coronary artery disease such as total and LDL-C levels was observed (29). Also, our study showed the reduction of SBP and serum TG levels compared to the control group.…”
Section: Discussionsupporting
confidence: 66%
“…Likewise, reduced blood pressure in the NAC treated group was observed in our study as well. The combinational effects of L-argentine and NAC on the level of blood pressure in patients with diabetic nephropathy was studied by Martina et al (29). They showed that L-arginine, is precursor for nitric oxide biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-over placebo-controlled study in elderly hypertensives (average age 69) treated with ACE inhibitors found that supplementing NAC at 600 mg three times daily amplified the blood pressure control achieved; 24-h blood pressure averaged 9 mmHg (systolic) and 6 mmHg (diastolic) lower when NAC was being administered-a very substantial effect (Barrios et al 2002). Another controlled trial evaluated a combination of 1200 mg daily of cysteine and 1200 mg arginine, given for 6 months, to type 2 diabetic (median age 64) (Martina et al 2008). As compared to response in the placebo group, the patients receiving this joint supplementation achieved reductions in systolic, diastolic, and mean blood pressure, various markers of endothelial activation, and plasma C-reactive protein, as well an improvement in endothelium-dependent vasodilation.…”
Section: Supplemental Nac In Aging Humans and Rodents Provides Versatmentioning
confidence: 99%
“…From previous studies, it was found that L-arginine can reduce heartdisease and pulmonary disease in rats and reverse the progressionof atherosclerosis in rabbits (Sheridan et al, 1998;Hayashi et al 2005). Watermelon is a diuretic and was a homeopathic treatment for kidney patients before dialysis became widespread.Also,it was found that oral L-arginine supplementation decrease brachial Blood pressure via improved endothelial NO productionin adults with prehypertension and hypertension (Palloshi et al,2004, Siani et al,2000, Martina et al,2008) However, in this study the effect of water melon on the pulse rate and blood pressure in healthy individual of Bingham University,Nasarawa state…”
Section: Introductionmentioning
confidence: 61%